(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Output Voltage Of The Renewable Energy Sources Such As Solar Is Very Low Which Is Not Sufficient To Drive The Loads In Practical. To Increase The Voltage Level, There Are Various Boost Converter Configurations Available In The Literature. The Significant Structure Is The Quadratic Boost Converter Which Has So Many Advantages Than The Conventional Converters. In This Paper, Novel Quadratic Boost Converter Is Proposed And Implemented In Hardware Prototype And The Experimental Results Are Compared With The Designed Values. The Results Show That The Proposed Converter Is Having Similar Results In Both Calculated And Real Time Values With Higher Efficiency.